Sidik Lintas Karakter Produksi dengan Karakter Vegetatif Pada Aksesi Pinang Bolaang Mongondow - MIFTAHORRACHMAN MIFTAHORRACHMAN (Pusat Penelitian dan Pengembangan Perkebunan, 2009)
Path Analysis of Yield with Vegetative Characters of Arecanut Accession from Bolaang MongondowThe research was conducted from May 2008 to October 2009 at Kayuwatu Experimental Garden, Manado, North Sulawesi Province. The purpose was to evaluate the direct and indirect effect of vegetative characters on yield character of Bolmong arecanut accession. Path analysis method was used in this experiment. The research result showed that from nine characters, there are four characters had direct effect on yield. They were, number of leaves, number of leafscars, upper inter-nodes, and middle internode. These characters had better relationship with yield character than other characters.